Worldwide Recessions and Herding Behaviour: A Comparative Analysis of Three Countries - Nurtantyo Pratomo Suyadi; Zaäfri Ananto Husodo (Green Publisher Indonesia, 2024)
The general suggestion that behavioral science plays a part in creating abnormalities within the financial sector has been studied and proposed many times in the past. This study aims to prove the existence of behavioral sciences, specifically herding behavior, in three countries with different market conditions: Indonesia (Emerging), Vietnam (Frontier), and the United States (Developed). We developed our methodology using quantile regression to study the existence of herding behavior, and our findings were as follows: (1) As expected, the US didn’t have any indication of a statistically significant herding presence; they do, however, indicate an insignificant presence of herding behavior in the post-covid period under bearish conditions (2) Vietnam does not indicate significant herding tendencies, (3) Surprisingly, Indonesia did not exhibit statistically significant herding presence, but both Indonesia and Vietnam exhibited the slight presence of herding behavior but still relatively insignificant.